Interpretative frameworks of the social in the living of the «new poverty» - Serrano Pascual, Araceli; Parajuá Navarrete, Daniel; Zurdo Alaguero, Ángel (Cuadernos de Relaciones Laborales, 2013)
By mean of qualitative empirical evidence, this article analyzes how the so called «new poor» constructs interpretive frameworks that are linked to different aspects related to social organization, inequality, the process of social polarization, impoverishment, as well as their capacity for political agency. The evidence illustrates the production of an ambivalent and nuanced process of breaking myths on which important aspects of the development of the capitalist model is established (myths of progress, meritocracy, middleclass society, or the consumption as a way of social integration). In addition, new interpretive frameworks are evaluated supporting the emerging model established in self-responsibility, guilt, fragmentation of the collective poor, and their want to conceal their own poverty.